Contralateral Risk-Reducing Mastectomy: Review of Risk Factors and Risk-Reducing Strategies. (27th January 2015) - Basu, N. N.; Barr, L.; Ross, G. L.; Evans, D. G.
Abstract : Rates of contralateral risk-reducing mastectomy have increased substantially over the last decade. Surgical oncologists are often in the frontline, dealing with requests for this procedure. This paper reviews the current evidence base regarding contralateral breast cancer, assesses the various risk-reducing strategies, and evaluates the cost-effectiveness of contralateral risk-reducing mastectomy.